Statistical consulting in the healthcare professions: A model of student‐led consulting services. Issue 1 (8th December 2022) - Kaseda, Erin T.; Graupman, Emily E.; Vincent, Samuel; Faith, Reid; Howe, Meghan M.; Dykins, Madison; Beussink, Courtney N.; Khan, Aaminah; Grotkowski, Karolina; Miller, Steven A.
Abstract : Statistical consulting is a common and vital activity undertaken by those with advanced statistical training but may not be widely available to health professionals and trainees without access to dedicated statistical consulting cores. Here, we present a novel model of statistical consulting used by a student chapter of the American Statistical Association housed in a graduate health professions university. This student‐led organization provides statistical consulting services for faculty, staff and students university‐wide. Information on the methods of advertising consulting services, the role of a professional statistician faculty advisor, resources available to consultants and university community members and the ways in which consulting services were adapted to address the barriers introduced by the COVID‐19 pandemic are addressed. Data from 108 consults performed over the past two and a half years with 88 different consultees are analysed and discussed. This article outlines an innovative model of student‐led statistical consultation for healthcare professionals and trainees and aims to provide a template for future student‐led organizations who similarly aim to perform university statistical consultations.